The Role of Childhood Trauma in a Schizophrenic Patient - Jessica, Lia; Sitawati, Andini Dyah; Nyoman Sumiat (Jurnal Psikiatri Surabaya, 2023)
Introductions: Schizophrenia is a severe mental disorder. Many factors could increase someone's risk of schizophrenia, including childhood trauma. There are many kinds of childhood trauma, including abuse and neglect. This report aims to emphasize the unwanted effects of childhood trauma in a schizophrenic patient and, therefore, the importance of its screening. Case: A hospitalized male hebephrenic patient was admitted and observed in Dr. Soetomo General Hospital for almost a month. The patient came to the hospital with a chief complaint of rage and grandiose delusion. He could neither eat nor sleep for about 2 weeks. He also had a history of neglect by his parents during childhood. Discussions: The patient, in this case suffered an acute psychosis that progressed into hebephrenic schizophrenia. He had a history of childhood trauma that made him vulnerable when faced with meaningful stress in his early adulthood. He had the grandiose delusion that was quite resistant with second generation of anti-psychotics and responded better with first generation of anti-psychotics. He was discharged on the 29th day of hospitalization and continued to take his antipsychotic medication orally at home. Conclusions: Childhood trauma has a huge contribution in risk for schizophrenia. Someone with history of childhood trauma tends to have vulnerability to a stress in adulthood that could make him fall into a psychosis and even schizophrenia. Therefore a screening for history of a childhood trauma is important.